Pengaruh Tingkat Ekonomi Orang Tua Dan Kedisiplinan Belajar Terhadap Prestasi Belajar Siswa Kelas Tinggi SD N 1 SimoTahun 2015/2016 - iswara, dita, Dra. Risminawati, M.Pd (2016)
This study aims to determine (1) the effect of the economic level of parents on learning achievement, (2) learning discipline influence on learning achievement, (3) the influence of parents and the level of discipline of learning on student achievement of high grade SD N 1 Simo. This study was a descriptive quantitative research with a conclusion through statistical analysis. The study population was all students of high grade (IV, V, VI) SD N 1 Simo totaling 113 students. The research sample included 30 students. The technique of collecting data using questionnaires and documentation. Data were analyzed using multiple linear regression analysis, t test, F test, the coefficient of determination, SR, SE, preceded by the prerequisite test analysis is the normality test and linearity test. Based on the analysis of multiple linear regression equation: Y = 52.760 + 0,612X1 + 0,178X2. The results of the data analysis with a significance level of 5% was obtained: (1) The level of parents' economic impact on student achievement. This is based on test t is known that tcount> ttable, namely 2.315> 2.048 and the significance value <0.05 is 0.028 with the relative contribution of 47.4% and the effective contribution of 14.6%. (2) Disciplinary learning effect on student achievement. This is based on test t is known that tcount> ttable namely 2.444> 2.048 and the significance value <0.05 is 0.021 with the relative contribution of 52.6% and the effective contribution of 16.2%. (3) The level of parents and the discipline of learning effect on student achievement. This is based on test F known that Fhitung> Ftable is 6.008> 3.32 and a significance value <0.05 is 0.007. Based on the calculation coefficient of determination is known that the influence of parents and the level of discipline of learning to student achievement contributed 47.4%, while 52.6% are influenced by other factors not examined Keywords: discipline learning, economic level of parents and learning achievement